Contribution to improve advance directives in Portugal - Macedo, João Carlos Gama Martins (2020)
This article explains the state of Advance Directives (concerning living wills in case of inability to express one) in Portugal. It explores the causes of the low number of registered advance directives and proposes a standard form, one of the ways to increase citizen adherence.